Siła upokorzenia. Avishaia Margalita refleksja o upokorzeniu i przyzwoitym społeczeństwie - Katarzyna Liszka (Studia Philosophica Wratislaviensia)
The article discusses Avishai Margalit’s philosophical reflection on humiliation developed in his book The Decent Society. It aims to show that while Margalit’s book focuses on the idea of a decent society as non-humiliating, and on “testing” selected institutions for humiliation, it also unfolds a complex reflection on humiliation as such. The purpose of the article is to reconstruct Margalit’s concept of humiliation and problematise selected aspects of it. I focus in particular on the relationships between humiliation and cruelty, humiliation and self-respect, respect and humiliation, institutional and private humiliation, as well as the theme of the humiliating perception of the other as less human and treating them as if they were not human. The argument is developed through reference to the texts of thinkers commenting on The Decent Society, among them Martin Krygier, Frederic Schick, and Dianne Taylor; those developing similar projects, like Judith Shklar, Richard Rorty, and Ute Frevent; and those bearing witness to humiliation, especially Audre Lorde and Frantz Fanon.